Tuning SQL Queries for Better Performance - S.N. , Kavitha (International Journal of Psychosocial Rehabilitation, 2020)
Structured Query Language (SQL) statements are used to retrieve data from the database. We can get the same results by writing SQL queries in a different way. But use of the best query is important when performance is considered. So we need SQL query tuning based on the business and user requirements. This paper is focusing on simple query tuning tips & tricks that can be applied to gain better performance.